Pemanfaatan Limbah Kulit Buah Kakao ( Theobroma cocoa L.) Sebagai Pupuk Bokhasi di Kelompok Tani Pleapuli - Maria Afriata Vini Yulia; Henderikus Darwin Beja; Yovita Yasintha Bolly (Jurnal Informasi Pengabdian Masyarakat, 2023)
Bloro Village is on of the village in Nita District, Sikka Regenecy, East Nusa Tenggara Province with the majority of the population working as farmers. The natural resources found in the plea puli farmer group are still very good, especially in the fields of agriculture and plantations, which are still very promising for Bloro village. One the natural resource that is abundant in this village in the field of agriculture and plantations is cocoa. Usually the farmer groups only use the cocoa shells are not used properly and correctly and only become useless waste. The method implemented by the author is through socialization and interview with farmers, namely explaining the benefits of cocoa shell waste s bokhasi fertilizer accompanied by training in making bokhasi fertilizer from cocoa shell waste.